Role of Legislation, Need of Strong Legal Framework and Procedures to Contest Effectively with Cybercrime and Money Laundering: Dr Aftab Ahmad Malik, Dr Mujtaba Asad, Dr Waqar Azeem - Dr Aftab Ahmad Malik; Dr Mujtaba Asad; Dr Waqar Azeem (International Journal for Electronic Crime Investigation, 2021)
There is need for a robust and strong legislation to tackle white Collar-crime is stressed, which is on the rise in both the public and private sectors. The effect of immoral and unlawful actions in government, notably high-level bribes, has crippled the financial and legislative bodies in their normal functioning. Bank frauds, money laundering, and cybercrimes are also on the rise, due to the widespread use of digital gadgets and the internet. The absence of strong network-security systems especially in the banking sector has caused great losses indeed. The goal of this study is multidimensional; more about the importance of applying strong regulations as well as morality and ethical principles. It has been argued in this paper that morality and ethical norms positively influence minimizing such crimes; if morality and ethics are coupled with strong legislation, it works as a Deterrence Force. It will undoubtedly be one of the most momentous global occurrences in recent history, long-term impacting culture, government operations, crime, economics, politics, and social relationships. The major role in combating the crime depends upon the existence of strong legislation capable of causing a reduction in the crime rate, which allows the investigators vast powers and collaboration with the prosecution and safeguarding the witnesses. The criminals are very well organized and use the most modern technology and IT equipment, therefore, the police, investigators, and prosecutors must have and be highly trained and equipped, similarly. appropriate methods and algorithms are required. We create a new method, a dynamic atomic shared memory for message communication. A properly stated method is proposed for message communication and then implemented. According to this method, owners can be changed dynamically, and their access to read and write also changes.